Design method of high performance asphalt mixture with surface macrostructure and internal dense waterproof

CN118724504BActive Publication Date: 2026-10-09JIANGSU SOBUTE NEW MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310323353.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-29
Publication Date
2026-10-09
Estimated Expiration
2043-03-29

AI Technical Summary

Technical Problem

[0007]针对现有沥青混合料设计方法对于沥青路面表面抗滑耐久性和抗渗水性能设计存在矛盾的问题,本发明提供了一种表面大构造且内部密实防水的高性能沥青混合料的设计方法

Benefits of technology

[0041] (1) The surface texture depth is large (the existing specifications require the texture depth to be ≤120mL/min and ≥0.5mm), which has good anti-skid performance, especially good anti-skid durability. The large surface texture depth can also reduce the generation of road surface water film in rainy weather to a certain extent, thereby greatly improving vehicle driving safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118724504B_ABST
    Figure CN118724504B_ABST
Patent Text Reader

Abstract

The application discloses a design method of high-performance asphalt mixture with surface large structure and internal dense waterproof. The design method introduces the index of the mutual contact degree (CCD) of coarse aggregate on the basis of the single index control of coarse aggregate forming a skeleton structure in the existing specification. Through the double index control, the asphalt mixture is ensured to form a stable skeleton interlocking structure, and the probability and stability of the coarse aggregate forming the skeleton interlocking structure are improved through the control of the passing rate under a specific sieve. Moreover, the low-temperature crack resistance is improved through the addition of additives and the control of the mineral aggregate porosity, the grading sensitivity is reduced by the synergistic control of multiple grading indexes, and finally the surface large structure and internal dense structure are realized. The asphalt mixture designed according to the design method has more excellent high-temperature deformation resistance, low-temperature crack resistance, water damage resistance, skid resistance and water permeability resistance when used in the surface layer of the asphalt pavement, and the service durability and driving safety of the asphalt pavement are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of road surface material design technology, specifically, it relates to a design method for a high-performance asphalt mixture with a large surface structure and a dense and waterproof interior. Background Technology

[0002] Asphalt concrete pavement has become the most important structural form in my country due to its advantages such as high mechanization in construction, comfortable and safe driving, convenient maintenance, rapid traffic opening, and recyclability. Asphalt pavement needs to withstand the environmental effects of high summer temperatures, severe winter cold, rain, and ultraviolet aging under vehicle loads for extended periods. Therefore, asphalt concrete is required to have good high and low temperature performance, skid resistance, impermeability, and aging resistance.

[0003] However, with the increasing traffic volume and heavy-duty vehicles on my country's roads, on the one hand, conventional asphalt concrete can no longer withstand the combined effects of the environment and heavy vehicle loads, resulting in a short service life; on the other hand, the performance of asphalt concrete is very sensitive to the mix proportion and construction quality, which often makes it difficult for the actual asphalt pavement to meet the design requirements. It is prone to various defects such as insufficient initial skid resistance, severe skid resistance attenuation, rutting, shoving, cracking, and water damage. Not only does its service life fall far short of the design level, but it also threatens driving safety.

[0004] Using high-performance admixtures or high-performance asphalt can improve the high and low temperature performance of asphalt mixtures to some extent and alleviate the aforementioned road distress problems, but it cannot solve the requirements of asphalt concrete on the road surface for impermeability and skid resistance. It needs to be improved in a coordinated manner through gradation design.

[0005] Asphalt mixtures used as the surface layer of asphalt pavements require consideration of both skid resistance and water permeability during design. Skid resistance is primarily related to the surface texture depth; a greater texture depth results in better skid resistance. To ensure water permeability, a lower porosity is generally desirable, which in turn leads to a shallower surface texture depth. Increasing the amounts of asphalt, fine aggregates, and mineral powder can reduce porosity and improve water permeability. However, during asphalt mixture compaction, excessive asphalt mastic may rise to the surface, reducing the texture depth. Therefore, these two aspects are contradictory in mixture gradation design.

[0006] Currently, the design methods for asphalt concrete surface layers of asphalt pavements are consistent with those for other surface layers, placing greater emphasis on the road performance of asphalt mixtures while lacking consideration for the surface functionality required for driving safety. In particular, the design control of the anti-skid durability and water permeability of the surface layer asphalt mixture needs to be optimized. Therefore, a method for designing asphalt mixtures that combine road performance, functionality, and construction stability remains a gap in the industry. Summary of the Invention

[0007] To address the contradiction between existing asphalt mixture design methods and the design of anti-skid durability and water-permeability properties of asphalt pavement surfaces, this invention provides a design method for high-performance asphalt mixtures with a large surface structure and a dense, waterproof interior. Asphalt mixtures designed according to this method, when used as surface layers of asphalt pavements, exhibit superior high-temperature deformation resistance, low-temperature crack resistance, water damage resistance, anti-skid properties, and water-permeability properties compared to conventional asphalt mixtures, thereby improving the service durability and driving safety of asphalt pavements.

[0008] The present invention specifically provides the following technical solutions:

[0009] A design method for a high-performance asphalt mixture with a large surface structure and a dense, waterproof interior, wherein the asphalt mixture includes coarse aggregate, fine aggregate, asphalt, additives, fibers, and mineral powder; the design method specifically includes the following steps:

[0010] S1. Using a 4.75mm sieve as the dividing line between coarse and fine aggregates, obtain the passing rates of each grade of coarse and fine aggregates under different sieve sizes, and determine the corresponding densities of each grade of coarse and fine aggregates, as well as asphalt, fiber and mineral powder.

[0011] S2. Based on the passing rate and density of each grade of coarse aggregate and fine aggregate under different sieve openings obtained in step S1, the blending ratio of each grade of coarse aggregate, fine aggregate and mineral powder is initially determined to obtain the synthetic mineral gradation.

[0012] S3. Based on the synthetic aggregate gradation obtained in step S2, determine the passing rate of the synthetic aggregate gradation under 4.75mm and 1.18mm sieves respectively; if both passing rates are within the control range, proceed to step S4; if at least one passing rate is not within the control range, return to step S2 to redesign and determine the blending ratio of each grade of coarse aggregate, fine aggregate and mineral powder.

[0013] S4. Based on the density obtained in step S1 and the synthetic aggregate gradation obtained in step S2, determine the coarse aggregate skeleton compaction gap ratio (VCA) of the synthetic aggregate gradation. DRC ;

[0014] S5. Based on the passing rate of the synthetic mineral gradation obtained in step S2 under a 0.075mm sieve, and in combination with the powder-to-binder ratio, determine the oilstone-to-aggregate ratio.

[0015] S6. Based on the synthetic aggregate gradation obtained in step S2 and the asphalt-aggregate ratio obtained in step S5, prepare asphalt mixture, determine the density and volume parameters of the asphalt mixture, and make a judgment.

[0016] If all three of the following conditions are met simultaneously, the sample is deemed qualified and proceeds to step S7. If at least one condition is not met, the sample is deemed unqualified and the process returns to step S2 to redesign and determine the blending ratios of each grade of coarse aggregate, fine aggregate, and mineral powder.

[0017] ① Coarse aggregate skeleton compaction gap ratio (VCA) DRC Coarse skeleton void ratio (VCA) of asphalt mixture mix The difference is ≥0.2%.

[0018] ② The contact density (CCD) of coarse aggregates in asphalt mixtures is ≥85%.

[0019] ③ The aggregate void ratio (VMA) of asphalt mixtures is between 17.5% and 24%;

[0020] S7. The qualified asphalt mixture obtained in step S6 is subjected to the following road performance verification.

[0021] If all five of the following road performance characteristics are qualified, the mixture is deemed qualified; if at least one road performance characteristic is unqualified, the mixture is deemed unqualified. The process then returns to step S2 to redesign and determine the blending ratios of each grade of coarse aggregate, fine aggregate, and mineral powder until an asphalt mixture meeting the following road performance characteristics is obtained:

[0022] a. The structural depth is greater than 0.9 mm.

[0023] b. Permeability coefficient is less than 30 mL / min

[0024] c. Dynamic stability at 60℃ is greater than 10,000 cycles / mm.

[0025] d. The maximum bending tensile strain at -10℃ is greater than 2800με.

[0026] e. Freeze-thaw splitting strength ratio greater than 90%.

[0027] Specifically, in step S3 above, the control range refers to a throughput of 23% to 31% for a 4.75mm sieve and a throughput of 15% to 22% for a 1.18mm sieve.

[0028] Specifically, in step S5 above, the powder-to-adhesive ratio is 0.8 to 2.8.

[0029] Specifically, in step S6 above, the degree of contact (CCD) between coarse aggregates in the asphalt mixture is calculated using the following formula (1):

[0030] CCD=(ρ G ×ρ GCA ) / VCA DRC (1)

[0031] Where, ρ GThis is the bulk density of the asphalt mixture (derived from the density determination in step S6 above), in g / cm³. 3 ;ρ GCA This is the bulk density of the coarse aggregate (derived from the density measurement in step S2 above), in g / cm³. 3 .

[0032] Generally, the coarse aggregate skeleton compaction gap ratio (VCA) in step S4 above is... DRC The coarse skeleton void ratio (VCA) of the asphalt mixture in step S6 above. mix The aggregate void ratio (VMA) of asphalt mixtures can be determined by referring to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011, T0705-2011).

[0033] Whether the coarse aggregate of asphalt mixture forms a skeleton structure is related to its high-temperature deformation resistance and skid resistance durability. The design method provided by this invention, under current specifications, only passes the "VCA" standard. DRC ≥VCA mix "Based on the single-index control of the coarse aggregate forming a skeleton structure in asphalt mixtures, the CCD (Cornering Density) index of coarse aggregates is introduced. Through dual-index control, a stable skeleton-interlocking structure is ensured in the asphalt mixture. Furthermore, by controlling the passing rates of 4.75mm and 1.18mm sieves to within the ranges of 23%–31% and 15%–22%, respectively, the probability and stability of the coarse aggregate forming a skeleton-interlocking structure are improved. Under this premise, on the one hand, additives enhance the toughness of the asphalt mastic and reduce the aging of toughening components during mixing, improving the low-temperature crack resistance of the asphalt mixture. On the other hand, by controlling the aggregate void ratio (VMA) ≥ 17.5%, more space is provided to accommodate the high-toughness asphalt mastic, increasing the percentage of high-toughness asphalt mastic while preventing its floating under compaction. This achieves a large surface structure and internal density in the asphalt mixture. Through the synergistic control of multiple gradation indices, the gradation fluctuation range of the asphalt mixture is reduced, lowering its gradation sensitivity."

[0034] Furthermore, in the above-mentioned asphalt mixture, the asphalt is SBS modified asphalt, and the mass percentage of SBS in the total asphalt is 2% to 6%.

[0035] Furthermore, in the above-mentioned asphalt mixture, the additive is a high-viscosity additive, which enables the added asphalt to have the following properties: ductility at 5℃ ≥30cm, elastic recovery rate ≥97%, and dynamic viscosity at 60℃ ≥400000Pa·s.

[0036] Preferably, the additive is added by direct dosing.

[0037] The aforementioned high-viscosity additives can be selected from products such as the high-viscosity modifier MA200 from Jiangsu Subote New Material Co., Ltd., or other commercially available products that can achieve the aforementioned modified properties.

[0038] Furthermore, in the aforementioned asphalt mixture, the fibers are selected from lignin fibers and / or polyester fibers.

[0039] Furthermore, in the above-mentioned asphalt mixture, the amount of mineral powder is 6% to 10% of the total amount of coarse aggregate, fine aggregate, and mineral powder.

[0040] Compared with existing technologies, the asphalt mixtures designed using the design method provided by this invention have the following advantages:

[0041] (1) The surface texture depth is large (the existing specifications require the texture depth to be ≤120mL / min and ≥0.5mm), which has good anti-skid performance, especially good anti-skid durability. The large surface texture depth can also reduce the generation of road surface water film in rainy weather to a certain extent, thereby greatly improving vehicle driving safety.

[0042] (2) The interior is dense. When used as a surface layer, it can effectively prevent rainwater from entering the interior of the asphalt mixture and reduce the incidence of water damage. It can also further prevent rainwater from entering the asphalt surface layer and damaging the interlayer bonding layer, thus avoiding damage between pavement layers.

[0043] (3) It has strong high-temperature resistance to deformation. The coarse aggregate forms a skeleton interlocking structure. The softening point of the asphalt mortar modified by the direct injection high viscosity additive is higher and the viscosity is greater under high temperature conditions. The asphalt mixture has excellent anti-rutting and anti-pushing performance.

[0044] (4) It has good low-temperature crack resistance. The asphalt mastic modified with direct-injection high-viscosity additives has high ductility, good toughness, and low aging during the production process. The larger aggregate void ratio can accommodate more high-toughness asphalt mastic, which enhances the crack resistance of asphalt mixtures.

[0045] (5) Improve the gradation stability of asphalt mixtures by controlling multiple gradation indicators in a coordinated manner, thereby reducing the gradation fluctuation range of asphalt mixtures and lowering the gradation sensitivity of asphalt mixtures. Attached Figure Description

[0046] Figure 1 This is a flowchart of a design method for a high-performance asphalt mixture with a large surface structure and a dense, waterproof interior, according to the present invention. Detailed Implementation

[0047] The design method for high-performance asphalt mixtures with large surface structure and dense, waterproof interior provided by this invention is as follows: Figure 1 As shown.

[0048] Specifically, it includes the following steps:

[0049] S1. Screen the coarse and fine aggregates and determine the density of each component.

[0050] Coarse and fine aggregates were sieved using a 4.75mm sieve as the boundary. The passing rates of each grade of coarse and fine aggregates under different sieve sizes were statistically analyzed, and the corresponding densities of each grade of coarse and fine aggregates, as well as asphalt, fiber, and mineral powder, were measured.

[0051] S2. Based on the throughput and density, the initial blending ratios of coarse aggregate, fine aggregate and mineral powder for each grade are determined to obtain the synthetic mineral gradation.

[0052] S3. Based on the gradation of the synthetic ore, determine the passing rate of the synthetic ore gradation under 4.75mm and 1.18mm sieves, respectively.

[0053] Specifically, if both pass rates are within the control range, proceed to step S4 below;

[0054] If at least one is outside the control range, return to step S2 above to redesign the proposed blending ratio to obtain a new synthetic mineral gradation.

[0055] The aforementioned control range specifically refers to a throughput of 23%–31% for a 4.75mm sieve and 15%–22% for a 1.18mm sieve.

[0056] S4. Determine VCA based on density and the gradation of the synthetic mineral aggregate. DRC .

[0057] S5. Based on the passing rate of the synthetic ore gradation under a 0.075mm sieve, and in conjunction with the powder-to-binder ratio, determine the oilstone ratio.

[0058] S6. Based on the gradation of the synthetic aggregate and the asphalt-aggregate ratio, prepare asphalt mixture, determine the density and volume parameters of the asphalt mixture, and make a judgment.

[0059] The judgment criteria include the following three aspects:

[0060] ① Coarse aggregate skeleton compaction gap ratio (VCA) DRC Coarse skeleton void ratio (VCA) of asphalt mixture mix The difference is ≥0.2%;

[0061] ② The contact degree (CCD) between coarse aggregates in the asphalt mixture is ≥85%;

[0062] ③ The aggregate void ratio (VMA) of asphalt mixtures is between 17.5% and 24%.

[0063] Specifically, if all three conditions above are met, the result is deemed qualified, and the following step S7 is continued.

[0064] If at least one condition is not met, the product is deemed unqualified, and the process returns to step S2 above to redesign and determine the blending ratio in order to obtain a new synthetic mineral gradation.

[0065] More specifically, in the above-mentioned judgment criteria, CCD is calculated according to the following formula:

[0066] CCD=(ρ G ×ρ GCA ) / VCA DRC (1)

[0067] Where, ρ G This is the bulk density of asphalt mixture, expressed in g / cm³. 3 ;ρ GCA This is the bulk density of coarse aggregate, expressed in g / cm³. 3 .

[0068] S7. Verify the road performance of the above asphalt mixture.

[0069] Road performance includes the following five aspects:

[0070] a. The structural depth is greater than 0.9 mm;

[0071] b. Permeability coefficient is less than 30 mL / min;

[0072] c. Dynamic stability at 60℃ is greater than 10,000 cycles / mm;

[0073] d. The maximum bending tensile strain at -10℃ is greater than 2800με;

[0074] e. Freeze-thaw splitting strength ratio greater than 90%.

[0075] Specifically, if all five road performance characteristics mentioned above are met, the mixture is deemed qualified, indicating that the asphalt mixture prepared in step S6 meets the requirements and is a high-performance asphalt mixture with both large surface structure and dense and waterproof interior.

[0076] If at least one road performance does not meet the requirements, it is deemed unqualified, and the process returns to step S2 above to redesign and determine the blending ratio to obtain a new synthetic aggregate gradation until an asphalt mixture that meets the above road performance requirements is obtained.

[0077] The embodiments of the present invention will now be described in detail. However, the present invention can be implemented in many different forms, and should not be construed as being limited to the specific embodiments set forth herein. Rather, these embodiments are provided to explain the principles of the invention and its practical application, thereby enabling others skilled in the art to understand the various embodiments of the invention and various modifications suitable for particular intended applications.

[0078] Example 1

[0079] The design method provided in this embodiment includes an asphalt mixture comprising two grades of coarse aggregate (10mm-13mm and 5mm-10mm), two grades of fine aggregate (3mm-5mm and 0-3mm), SBS modified asphalt, direct-injection high-viscosity additives, lignin fibers, and mineral powder.

[0080] First, the coarse and fine aggregates are screened, and the density of each component is measured.

[0081] Coarse and fine aggregates were sieved using a 4.75mm sieve as the boundary. The passing rates of each grade of coarse and fine aggregates under different sieve sizes were statistically analyzed, and the corresponding densities of each grade of coarse and fine aggregates, as well as asphalt, fiber, and mineral powder, were measured.

[0082] The screening curves of coarse and fine aggregates and mineral powder are shown in Table 1 below.

[0083] Table 1. Screening curves of coarse aggregate, fine aggregate, and mineral powder.

[0084]

[0085] The densities of coarse and fine aggregates and mineral powder are shown in Table 2 below.

[0086] Table 2 Density of coarse and fine aggregates and mineral powder

[0087]

[0088] In this embodiment, the relative density of the SBS asphalt used to prepare the asphalt mixture is 1.013 g / cm³. 3 The relative density of the mineral powder is 2.802 g / cm³. 3 The relative density of lignin fibers is taken as 0.351 g / cm³. 3 .

[0089] Secondly, the preliminary blending ratios of coarse aggregate, fine aggregate, and mineral powder for each grade are shown in Table 3 below.

[0090] Table 3. Proportions of coarse and fine aggregates and mineral powder

[0091]

[0092] Based on the sieving curves of coarse aggregate, fine aggregate and mineral powder in Table 1 and the blending ratios of coarse aggregate, fine aggregate and mineral powder in Table 3, the synthetic mineral gradation shown in Table 4 is obtained.

[0093] Table 4. Gradation of Synthetic Minerals

[0094]

[0095] Next, based on the synthetic mineral gradation obtained in Table 4, the passing rates under 4.75 mm and 1.18 mm sieves are 29.9% and 16.8%, respectively. It is determined that the passing rates of the synthetic mineral gradation under 4.75 mm and 1.18 mm sieves are in the range of 23% to 31% and 15% to 22%, respectively. Both passing rates are within the control range, so the following steps can be continued.

[0096] The fourth step is to calculate the VCA based on the density and gradation of the synthetic aggregate, referring to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011, T0705-2011). DRC The result was 39.1%.

[0097] The fifth step is to determine the asphalt-aggregate ratio based on the passing rate of the synthetic aggregate gradation through a 0.075mm sieve, which is 11.8%. Combined with the powder-to-binder ratio, it is initially proposed to be 2.3. According to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011, T0705-2011), the asphalt-aggregate ratio is calculated to be 6.2%.

[0098] The SBS content in the SBS modified bitumen is 4%, and the amount of SBS bitumen used is 5.6% of the aggregate.

[0099] The dosage of the high-viscosity and high-elasticity additive is 0.6% of the mineral aggregate. The specific properties of the modified high-viscosity and high-elasticity asphalt are: ductility at 5℃ is 40cm, elastic recovery rate is 98.1%, and dynamic viscosity at 60℃ is 460000Pa·s.

[0100] The fiber is specifically lignin fiber, and its usage is 0.4% of the mineral.

[0101] Step 6: Based on the synthetic aggregate gradation and asphalt-aggregate ratio, prepare asphalt mixture, determine the density and volumetric parameters of the asphalt mixture, and calculate the VCA (Volume Capacity) with reference to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011, T0705-2011). mix And VMA, and calculate CCD according to the above formula (1); and make a judgment, the results are shown in Table 5 below.

[0102] Table 5 Results of volumetric parameters of asphalt mixture

[0103]

[0104] If all three conditions are met, the test is considered successful, and the following steps can be continued.

[0105] Finally, referring to the corresponding test methods in the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011, T0705-2011), the road performance of the above asphalt mixture was verified, and the results are shown in Table 6.

[0106] Table 6. Test methods and road performance of asphalt mixtures

[0107]

[0108] All five road performance characteristics mentioned above are met, indicating that the asphalt mixture prepared in the above steps meets the requirements and is a high-performance asphalt mixture with both large surface structure and dense and waterproof interior.

[0109] Example 2

[0110] The design method provided in this embodiment includes an asphalt mixture comprising three grades of coarse aggregate (11mm-16mm, 6mm-11mm, and 4mm-6mm), two grades of fine aggregate (0-4mm), SBS modified asphalt, direct-injection high-viscosity additives, lignin fiber, and mineral powder. The four grades of aggregate are hot aggregates screened by a hot aggregate screen at the mixing plant.

[0111] First, the coarse and fine aggregates are screened, and the density of each component is measured.

[0112] Coarse and fine aggregates were sieved using a 4.75mm sieve as the boundary. The passing rates of each grade of coarse and fine aggregates under different sieve sizes were statistically analyzed, and the corresponding densities of each grade of coarse and fine aggregates, as well as asphalt, fiber, and mineral powder, were measured.

[0113] The screening curves of coarse and fine aggregates and mineral powder are shown in Table 7 below.

[0114] Table 7 Screening curves of coarse aggregate, fine aggregate, and mineral powder

[0115]

[0116] The densities of coarse and fine aggregates and mineral powder are shown in Table 8 below.

[0117] Table 8 Density of coarse and fine aggregates and mineral powder

[0118]

[0119] In this embodiment, the relative density of the SBS asphalt used to prepare the asphalt mixture is 1.013 g / cm³. 3 The relative density of the mineral powder is 2.802 g / cm³. 3 The relative density of lignin fibers is taken as 0.351 g / cm³. 3 .

[0120] Secondly, the preliminary blending ratios of coarse aggregate, fine aggregate, and mineral powder for each grade are shown in Table 9 below.

[0121] Table 9. Proportions of coarse and fine aggregates and mineral powder

[0122]

[0123] Based on the sieving curves of coarse aggregate, fine aggregate and mineral powder in Table 7 and the blending ratios of coarse aggregate, fine aggregate and mineral powder in Table 9, the synthetic mineral gradation shown in Table 10 is obtained.

[0124] Table 10 Synthetic Mineral Gradation

[0125]

[0126] Secondly, based on the synthetic mineral gradation obtained in Table 10, the passing rates under 4.75 mm and 1.18 mm sieves are 23.6% and 13.1%, respectively. It is determined whether the passing rates of the synthetic mineral gradation under 4.75 mm and 1.18 mm sieves are within the range of 23% to 31% and 15% to 22%, respectively.

[0127] The pass rate through the 1.18mm sieve was outside the control range, indicating that the synthetic gradation was unqualified. We returned to the second step above and re-determined the blending ratio of coarse and fine aggregates and mineral powder, as shown in Table 11 below.

[0128] Table 11. Proportions of coarse and fine aggregates and mineral powder

[0129]

[0130] Based on the sieving curves of coarse aggregate, fine aggregate and mineral powder in Table 7 and the revised blending ratios of coarse aggregate, fine aggregate and mineral powder in Table 11, the synthetic mineral gradation shown in Table 12 is obtained.

[0131] Table 12 Synthetic Mineral Gradation

[0132]

[0133] Based on the synthetic mineral gradation obtained in Table 12, the passing rates under 4.75 mm and 1.18 mm sieves are 26.4% and 16.4%, respectively. It is determined that the passing rates of the synthetic mineral gradation under 4.75 mm and 1.18 mm sieves are in the range of 23%–31% and 15%–22%, respectively. Both passing rates are within the control range, so the following steps can be continued.

[0134] The fourth step is to calculate the VCA based on the density and pass rate of the synthetic aggregate gradation, referring to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011, T0705-2011). DRCThe result was 38.4%.

[0135] Based on the passing rate of the synthetic aggregate gradation through a 0.075mm sieve, specifically 10.5%; combined with the powder-to-binder ratio, initially proposed to be 2, and calculated according to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011, T0705-2011), the asphalt-aggregate ratio is determined to be 6.3%.

[0136] The SBS content in the SBS modified bitumen is 4%, and the amount of SBS bitumen used is 5.7% of the aggregate.

[0137] The dosage of the high-viscosity and high-elasticity additive is 0.6% of the mineral aggregate. The modified high-viscosity and high-elasticity asphalt has the following properties: ductility at 5℃ is 43cm, elastic recovery rate is 97.2%, and dynamic viscosity at 60℃ is 430000Pa·s.

[0138] The fiber is lignin fiber, and its usage is 0.4% of the mineral.

[0139] The fifth step involves preparing asphalt mixtures based on the synthetic aggregate gradation and asphalt-aggregate ratio that meet the pass rate requirements. The density and volumetric parameters of the asphalt mixture are then determined, and the VCA is calculated with reference to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011, T0705-2011). mix And VMA, and calculate CCD according to the above formula (1); and make a judgment, the results are shown in Table 13 below.

[0140] Table 13 Results of volumetric parameters of asphalt mixtures

[0141]

[0142] Among the three conditions mentioned above, the coarse skeleton void ratio (VCA) of the asphalt mixture is... mix If the aggregate void ratio (VMA) of the asphalt mixture does not meet the requirements, it is deemed unqualified. The amount of aggregate with a diameter of 4 mm to 6 mm is increased, and the synthetic gradation is re-determined, as shown in Table 14 below.

[0143] Table 14. Proportions of coarse and fine aggregates and mineral powder

[0144]

[0145] Based on the sieving curves of coarse aggregate, fine aggregate and mineral powder in Table 9 and the blending ratios of coarse aggregate, fine aggregate and mineral powder in Table 14, the synthetic mineral gradation shown in Table 15 is obtained.

[0146] Table 15 Synthetic Mineral Gradation

[0147]

[0148] Based on the synthetic mineral gradation obtained in Table 15, the passing rates under 4.75 mm and 1.18 mm sieves are 27.7% and 15.1%, respectively. It is determined that the passing rates of the synthetic mineral gradation under 4.75 mm and 1.18 mm sieves are in the range of 23%–31% and 15%–22%, respectively. Both passing rates are within the control range, so the following steps can be continued.

[0149] Based on density and synthetic mineral gradation, VCA again DRC The result was 41.2%.

[0150] Based on the latest synthetic aggregate gradation, the passing rate under a 0.075mm sieve is 10.7%; combined with the powder-to-binder ratio, it is initially proposed to be 2. According to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011, T0705-2011), the asphalt-aggregate ratio is calculated to be 6.3%.

[0151] The SBS content in the SBS modified bitumen is 4%, and the amount of SBS bitumen used is 5.7% of the aggregate.

[0152] The dosage of the high-viscosity and high-elasticity additive is 0.6% of the mineral aggregate. The modified high-viscosity and high-elasticity asphalt has the following properties: ductility at 5℃ is 42cm, elastic recovery rate is 97.7%, and dynamic viscosity at 60℃ is 410000Pa·s.

[0153] The fiber is lignin fiber, and its usage is 0.4% of the mineral.

[0154] Asphalt mixtures were prepared based on the gradation of the synthetic aggregates and the asphalt-aggregate ratio. The density and volume parameters of the asphalt mixtures were measured and judged. The results are shown in Table 16 below.

[0155] Table 16 Results of volumetric parameters of asphalt mixtures

[0156]

[0157] If all three conditions are met, the test is considered successful, and the following steps can be continued.

[0158] Finally, referring to the corresponding test methods in the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011, T0705-2011), the road performance of the above asphalt mixture was verified, and the results are shown in Table 17.

[0159] Table 17 Test methods and road performance of asphalt mixtures

[0160]

[0161] All five road performance characteristics mentioned above are met, indicating that the asphalt mixture prepared by the above steps meets the requirements and is a high-performance asphalt mixture with both large surface structure and dense and waterproof interior.

Claims

1. A design method for a high-performance asphalt mixture with a large surface structure and a dense, waterproof interior, characterized in that, Including the following steps: S1. Using a 4.75 mm sieve as the dividing line between coarse and fine aggregates, obtain the passing rates of each grade of coarse and fine aggregates under different sieve sizes, and determine the corresponding densities of each grade of coarse and fine aggregates, as well as asphalt, fiber and mineral powder. S2. Based on the passing rate and density of each grade of coarse aggregate and fine aggregate under different sieve openings obtained in step S1, the blending ratio of each grade of coarse aggregate, fine aggregate and mineral powder is initially determined to obtain the synthetic mineral gradation. S3. Based on the synthetic mineral aggregate gradation obtained in step S2, determine the passing rate of the synthetic mineral aggregate gradation under 4.75 mm and 1.18 mm sieves respectively; if both passing rates are within the control range, proceed to step S4; if at least one passing rate is not within the control range, return to step S2 to redesign and determine the blending ratio of each grade of coarse aggregate, fine aggregate and mineral powder. The control range refers to a throughput of 23%~31% with a 4.75 mm sieve aperture and a throughput of 15%~22% with a 1.18 mm sieve aperture. S4. Based on the density obtained in step S1 and the synthetic aggregate gradation obtained in step S2, determine the coarse aggregate skeleton compaction gap ratio (VCA) of the synthetic aggregate gradation. DRC ; S5. Based on the passing rate of the synthetic mineral aggregate gradation obtained in step S2 under a 0.075 mm sieve, and in conjunction with the powder-to-binder ratio, determine the oilstone-to-aggregate ratio; wherein the powder-to-binder ratio is 0.8~2.

8. S6. Based on the synthetic aggregate gradation obtained in step S2 and the asphalt-aggregate ratio obtained in step S5, prepare asphalt mixture, determine the density and volume parameters of the asphalt mixture, and make a judgment. If all three of the following conditions are met simultaneously, the sample is deemed qualified and proceeds to step S7. If at least one condition is not met, the sample is deemed unqualified and the process returns to step S2 to redesign and determine the blending ratios of each grade of coarse aggregate, fine aggregate, and mineral powder. ① Coarse aggregate skeleton compaction gap ratio (VCA) DRC Coarse skeleton void ratio (VCA) of asphalt mixture mix The difference is ≥0.2%. ② The contact density (CCD) of coarse aggregates in asphalt mixtures is ≥85%. The CCD is calculated using the following formula (1): CCD=(ρ G ×ρ GCA ) / VCA DRC (1) In equation (1), ρ G This is the bulk density of asphalt mixture, expressed in g / cm³. 3 ;ρ GCA This is the bulk density of coarse aggregate, expressed in g / cm³. 3 ; ③ The aggregate void ratio (VMA) of asphalt mixtures is between 17.5% and 24%; S7. The qualified asphalt mixture obtained in step S6 is subjected to the following road performance verification. If all five of the following road performance characteristics are qualified, the mixture is deemed qualified; if at least one road performance characteristic is unqualified, the mixture is deemed unqualified. The process then returns to step S2 to redesign and determine the blending ratios of each grade of coarse aggregate, fine aggregate, and mineral powder until an asphalt mixture meeting the following road performance characteristics is obtained: a. The structural depth is greater than 0.9 mm. b. Permeability coefficient is less than 30 mL / min c. Dynamic stability at 60℃ is greater than 10,000 cycles / mm. d. The maximum bending tensile strain at -10℃ is greater than 2800 µε. e. Freeze-thaw splitting strength ratio greater than 90%.

2. The design method according to claim 1, characterized in that, In the asphalt mixture, the asphalt is SBS modified asphalt, and the mass percentage of SBS in the total asphalt is 2% to 6%.

3. The design method according to claim 1, characterized in that, In the asphalt mixture, the additive is a high-viscosity additive, which enables the asphalt to have the following properties: ductility at 5℃ ≥30 cm, elastic recovery rate ≥97%, and dynamic viscosity at 60℃ ≥400000 Pa·s.

4. The design method according to claim 3, characterized in that, The additive is added via direct dosing.

5. The design method according to claim 3, characterized in that, The additive is a high-viscosity modifier, MA200.

6. The design method according to claim 1, characterized in that, In the asphalt mixture, the fibers are selected from lignin fibers and / or polyester fibers.

7. The design method according to claim 1, characterized in that, In the asphalt mixture, the amount of mineral powder is 6% to 10% of the total amount of coarse aggregate, fine aggregate, and mineral powder.

Citation Information

Patent Citations

  • Design method of a high-toughness ultrathin asphalt wearing layer mixture

    CN109657421A

  • Mix proportion design method of ultrathin wearing layer asphalt mixture

    CN110904764A